An Empirical Study to Evaluate the Effect of Stress on Employee Performance in Hybrid Work Settings Within Project Management Organisations in Azerbaijan - Ahmadov, Rauf (Digital Repository of Theses, 2026)
The rapid expansion of hybrid work models has introduced a new performance pressure for employees, which is a combine physical, social, technological, and psychological stressor. While these organizations view hybrid systems as efficient, they also focus on create unique challenges in project driven environment. The study investigates how work environment, team dynamics, job roles, reliance structures, and technological factors jointly shape employee performance. Through the examination of these constructs together, the research advances at understanding of hybrid stress performance dynamics in a complex organizational context. Theories used were Job Demand Control model, Person-Environment Fit theory and the Social Exchange Theory. A quantitative approach was employed using a structured questionnaire distributed to 373 employees engaged in a hybrid project management setting at Azerbaijan the instrument measured five constructs, such as work environment, team dynamics, job roles, reliance structures and technological factors in relation to employee performance. The descriptive statistics established distributional patterns while the correlation and regression analysis assessed both bivariate relationship and unique predictor effects. Data triangulation enhanced internal validity by integrating descriptive as well as correlational multivariate evidence across the stress performance framework. The findings indicate a strong positive correlation between employee performance and work environment (r=0.843), team dynamics (r=0.857) and technological factors (r=0.824). Job role (r=0.136) and individual reliance (r=0.225) indicated weaker association but remained significant. Regression analysis revealed high model fit (R=0.927) while the team dynamics (β=0.424) and work environment (β=0.400) exerted the strongest effects with reliance, role clarity and technological contributing incrementally. The study concluded that hybrid stress is a multidimensional factor which game and work environment emerging as the most influential performance levers. While technology is strongly linked to performance but shares variance with the contextual and social conditions. Furthermore, role clarity and reliance patterns though weaker predictors, remain important for resilience in hybrid work. The model’s explanatory strength indicates robust construct representation. The organizations therefore must prioritize supportive environment, adaptive technological integration and effective collaboration to enhance employee performance in hybrid models.